Comparative analysis of fault tolerance models and their challenges in cloud computing - Dhingra, Mridula; Gupta, Neha (International Journal of Engineering and Technology, 2017)
Cloud Computing is a vital platform for viable and non-viable clients. It provides the reliable services to clients through data centers which contains servers, storage etc. One of the major challengein cloud computing environment is that services should be run without errors or faults. In cloud computing environment various computations are run on real time applications so that chances of errors becomes high, for these reasons applications running in cloud environment should be reliable and must have the ability of fault tolerance. In this paper, authors have discussed many fault tolerance techniques and compared various model of fault tolerance.